The value of targeted CXCR4 18F-AlF-NOTA-pentixafor PET/CT for subtyping primary aldosteronism - Peng, Yushi; Chen, Fangansheng; Yao, Rui; Lan, Junping; Fu, Yinuo; Ye, Kaifeng; Wang, Zhiqiang; Zhao, Qianxiu; Ji, Xiaowei; Xia, Kang; Zhu, Guoqing; Zheng, Kewen; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThe study aimed to investigate the diagnostic value of 18F-AlF-NOTA-Pentixafor PET/CT in subtyping primary aldosteronism (PA).MethodsThis study enrolled 88 patients with PA or nonfunctional adenoma (NFA) for 18F-Pentixafor PET/CT scan. Of these, 20 patients underwent adrenal venous sampling (AVS), and 65 underwent adrenalectomy and postoperative follow-up.ResultsIn 88 patients, 76 were diagnosed with unilateral PA (UPA), 4 were diagnosed with bilateral PA (BPA), and 8 were diagnosed with NFA, resulting in a total of 95 lesions. To identify UPA, visual analysis received a specificity of 94.12% and a sensitivity of 89.74%. The optimal cutoff values for SUVmax at 5.45, the lesion-to-normal adrenal ratio (LAR) at 1.43, and lesion-to-liver ratio (LLR) all yielded a specificity of 100% and a sensitivity of 79.49%, 83.33%, and 80.77%, respectively. In 15 adrenal lesions with similar uptake to contralateral and adjacent normal adrenal tissue (defined as warm lesions), 7 were confirmed as UPA, 4 were confirmed as BPA, and 4 were confirmed as NFA. Furthermore, among the 20 patients who underwent AVS, the concordance rate of AVS and PET/CT visual analysis for PA subtyping was 65.00%.ConclusionsThe CXCR4-targeted 18F-AlF-NOTA-pentixafor PET/CT is a valuable noninvasive tool for diagnosing UPA, demonstrating high sensitivity and specificity. More attention should be paid to warm adrenal lesions for their high diagnostic ambiguity probability.